Possible applications for replicating HIV 1 vectors - Das, Atze T (2010)
Since its discovery some 25 years ago, much has been learned about HIV type 1 and the molecular details of its replication cycle. This insight has been used to develop lentiviral vector systems that have advantages over conventional retroviral vector systems. For safety reasons, the lentiviral vector systems are replication incompetent and the risk of generating a replication competent virus has been minimized. Nevertheless, there may be certain applications for replication competent HIV based vector systems, and we will review our activities in this particular field. This includes the generation of a conditionally replicating HIV 1 variant as a safe live attenuated virus vaccine, the construction of mini HIV variants as cancer selective viruses for virotherapy against leukemia, and the use of a conditionally live anti HIV gene therapy vector. Although safety concerns will undoubtedly remain for the use of replication competent HIV based vector systems, some of the results in cell culture systems are very promising and warrant further testing in appropriate animal models.